Indicator for a monitoring of Germany's landscape attractiveness. (November 2018) - Walz, Ulrich; Stein, Christian
Abstract: Landscape attractiveness describes a landscape's capacity for nature-based recreation. In this contribution an indicator is proposed, which was derived from eight equivalent parameters for the determination of human use and landscape structure. It was supposed to be applicable with already existing geodata. A five-tier scale hereby assists with the requirement to provide a coarse classification of municipalities in regards to landscape attractiveness. The data provides a first overview, e.g. for the planning process regarding major powerlines as part of the German 'Energiewende', the national transformation policy towards a sustainable energy production, or as a measure for the meaning and potential of a region for nature-based tourism. The result maps clearly show that the selected eight parameters are suitable for the depiction of the most relevant features of an attractive landscape. Hereby, the coastal and alpine regions, as well as the low mountain regions and lakelands can be clearly distinguished from regions with intensive settlements and agricultural use. An evaluation of the provision of cultural ecosystem services for landscape-oriented recreation becomes hereby possible.